2022
DOI: 10.1071/am21032
|View full text |Cite
|
Sign up to set email alerts
|

A 6-year study of mitigating koala roadkill during an upgrade of the Pacific Highway at Lindsay’s cutting, Coffs Harbour New South Wales

Abstract: This 6-year study aimed to monitor a local koala population and koala protection/mitigation measures before, during and after a major upgrade to the Pacific Highway at Lindsay’s cutting near Coffs Harbour in northern coastal New South Wales. This represents the scale of the individual koala interacting with traffic on a primary road within a well-studied Local Government Area for koalas. We also collected records of koala road injury and death from local wildlife carers. The principal findings were that, befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Road mortality is a significant threat to wildlife populations (Fahrig and Rytwinski 2009) including koalas across their range (Lunney et al 2022a(Lunney et al , 2022bMelzer and Black 2022), with a reported 300 vehicle related deaths per year in South East Queensland alone (Dique et al 2003b;de Oliveira et al 2014). Major roads, with higher volumes and speeds of traffic can act as movement barriers, decreasing habitat connectivity and gene flow (Dudaniec et al 2013).…”
Section: Roads As a Major Anthropogenic Threatmentioning
confidence: 99%
“…Road mortality is a significant threat to wildlife populations (Fahrig and Rytwinski 2009) including koalas across their range (Lunney et al 2022a(Lunney et al , 2022bMelzer and Black 2022), with a reported 300 vehicle related deaths per year in South East Queensland alone (Dique et al 2003b;de Oliveira et al 2014). Major roads, with higher volumes and speeds of traffic can act as movement barriers, decreasing habitat connectivity and gene flow (Dudaniec et al 2013).…”
Section: Roads As a Major Anthropogenic Threatmentioning
confidence: 99%
“…Habitat restoration programs can be conducted at different scales, individually or collectively, and can be supported through local, state and commonwealth government initiatives or grants or philanthropic organisations. Disease and injury management has been largely taken up by local volunteer groups operating under licence from the NSW State government (Lunney et al 2022a). Vehicle strike hotspot management is the responsibility of the State government for highways, but the management of local and arterial roads falls to local councils.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, wildlife road crossing structures are often installed for threatened species (e.g., Mansergh & Scotts, 1989). In eastern Australia, concern about the impacts of new roads on the threatened koala has been responsible for the installation of vast lengths of road‐side fencing and large numbers of underpasses (e.g., Lunney et al, 2022; Taylor & Goldingay, 2003). Our study provides some insight into the effectiveness of this strategy for the koala and other threatened species.…”
Section: Discussionmentioning
confidence: 99%